Identification of Differential Genes Expression Profiles and Pathways of Bone Marrow Mesenchymal Stem Cells of Adolescent Idiopathic Scoliosis Patients by Microarray and Integrated Gene Network Analysis. Issue 10 (May 2016) - Zhuang, Qianyu; Mao, Wenzhe; Xu, Pengchao; Li, Hongling; Sun, Zhao; Li, Shugang; Qiu, Guixing; Li, Jing; Zhang, Jianguo
Abstract : Study Design: Microarray approach and integrated gene network analysis. Objective: To explore the differential genetic expression profile, gene ontology terms, and Kyoto Encyclopedia of Genes and Genomes pathways in bone marrow mesenchymal stem cells (BM-MSCs) of idiopathic scoliosis (AIS) and non-AIS controls. Summary of Background Data: The pathogenesis of adolescent AIS and the accompanying generalized osteopenia remain unclear. Our previous study suggested increased proliferation ability and decreased osteogenic differentiation ability of BM-MSCs of AIS. Therefore, we hypothesized that MSCs may play a significant role in the etiology and pathogenesis of AIS. Methods: In this study, microarray analysis was used to identify differentially expressed genes (DEGs) of BM-MSCs from AIS patients compared with those from healthy individuals. Comprehensive bioinformatics analyses were then used to enrich datasets for gene ontology and pathway. Based on the gene signal transduction network analysis of DEGs contained in significant pathways, 24 potential crucial genes were selected for validation by reverse transcription polymerase chain reaction. Results: There are 1027 previously unrecognized DEGs in BM-MSCs from AIS patients. Pathway analysis revealed dysregulated mitogen-activated protein kinase (MAPK) signaling pathway, PI3K-Akt signaling pathway, calcium signaling pathway, peroxisome proliferator-activated receptor (PPAR) signaling pathway, ubiquitin-mediated proteolysis, and Notch signaling pathway, all of which have been reported to play an important role in regulating the osteogenic or adipogenic differentiation of MSCs. Furthermore, gene signal transduction networks analysis indicated that mitogen-activated protein kinase kinase 1 (MAP2K1), SMAD family member 3 (SMAD3), homeobox C6 (HOXC6), heat shock 70kDa protein 6 (HSPA6), general transcription factor IIi (GTF2I), CREB binding protein (CREBBP), phosphoinositide-3-kinase, regulatory subunit 2 (PIK3R2), and dual specificity phosphatase 2 (DUSP2) may play essential roles in AIS pathogenesis and accompanied osteopenia. Conclusion: This study reports the differential genes expression profiles of BM-MSCs from AIS patients and related potential pathways for the first time. These previously unrecognized genes and molecular pathways might play a significant role in not only the causal mechanism of osteopenia in AIS, but also the AIS initiation and development. The identification of these candidate genes provides novel insight into the underlying etiological mechanisms of AIS. Level of Evidence : N/A Abstract : Supplemental Digital Content is available in the text